2018
DOI: 10.7557/14.4295
|View full text |Cite
|
Sign up to set email alerts
|

Innvandrerkvinners erfaringer med svangerskap, fødsel og barseltid i Norge - en kvalitativ studie

Abstract: Right to equal healthcare is statutory in Norway, but there is little knowledge of immigrant women's experiences of health- and welfare services during pregnancy and the portnatal period. Immigrant women are at higher risk for a number of complications related to this period. The purpose of this study was to acquire deeper insight into immigrant women's needs and experiences during their pregnancy, childbirth and the postnatal period in Norway. The study has a qualitative design using in-depth interviews of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…De 44 inkluderte artiklene ble sortert i åtte kategorier basert på tema (se appendiks 2). 42 artikler var publisert på engelsk og to på norsk (6,36). Åtte studier var kvalitative, resten kvantitative.…”
Section: Figur 1 Flytdiagram Over Litteratursøketunclassified
“…De 44 inkluderte artiklene ble sortert i åtte kategorier basert på tema (se appendiks 2). 42 artikler var publisert på engelsk og to på norsk (6,36). Åtte studier var kvalitative, resten kvantitative.…”
Section: Figur 1 Flytdiagram Over Litteratursøketunclassified
“…Research addressing the niche of migrant maternal health has mainly concluded that cultural diversity poses a challenge for the current Norwegian maternity care model (Lyberg et al, 2012 ). Other Norwegian studies on migrant maternal health address topics such as: nutrition (Garnweidner et al, 2013 ); domestic violence (Garnweidner-Holme et al, 2017 ); post-natal feeding practices (Wandel et al, 2016 ); risk of stillbirth (Vik et al ( 2019 ); and migrant women’s experiences and perceptions of services (Egge et al, 2018 ; Glavin & Sæteren, 2016 ; Herrero-Arias et al, 2020 ; Viken et al, 2015 ). This study adds to the body of research by exploring how immigrant women experience and navigate the Norwegian Maternal Health Service during pregnancy and childbirth.…”
Section: Introductionmentioning
confidence: 99%